A review on conventional and novel topical ocular drug delivery system - Rozi, Mohamad Faeznudin; Mohmad Sabere, Awis Sukarni (Kulliyyah of Pharmacy, International Islamic University Malaysia (IIUM), 2021)
Ocular drug delivery is a very challenging area for ophthalmologists and drug delivery scientists due to the structural and barrier complexity of the eye. Barriers such as different layers of cornea, sclera, conjunctival blood flow, and tear dilution limit the efficacy of drug delivery to the anterior part of the eye in addition to more barriers present to the po sterior part. Due to these, scientists have designed and studied various delivery systems to increase drug delivery and treatment efficacy to the eye. Among conventional ocular drug delivery systems, ophthalmic solution or eye drop is widely used and prefe rred by consumers. Conventional dosage forms available in the market are emulsion, suspension, ointment and polymeric gels. Several ocular formulations such as nano formulations, liposomes, ocular inserts, and ocular mini tablets are also being widely studied as future treatments to improve ocular drug delivery and as an alternative to conventional drug delivery. This review intends to summarise several conventional and novel topical formulations for ocular drug delivery.